Use of Medroxyprogesterone Acetate as a Contraceptive in conjunction with Early Postpartum Rubella Vaccination. Issue 5890 (24th November 1973) - Sharp, David S.; Macdonald, Helen
Abstract : During a 12-month period 170 women received early postpartum rubella vaccination. An injectable "depot" progestogen was given to each of these patients for contraceptive purposes at the same time as the vaccine was administered. Subsequent observations showed that the progestogen was effective as a contraceptive in this context and that it did not appear to affect the immune response of the patients to the vaccine.